UMP, Pahang SEDC forged ties to spur Pahang’s weaving industry - UMP, PNC
In an effort to boost Pahang’s weaving industry in Malaysia, Universiti Malaysia Pahang (UMP) joined forces with Pahang State Economic Development Corporation (SEDC) by signing a memorandum of understanding (MoU) at Sultan Haji Ahmad Shah Pahang Royal Weaving Development Complex in Kampung Soi, Kuantan on May 23, 2012.